Cognitive testing of a survey instrument to assess sexual practices, behaviours, and health outcomes: a multi-country study protocol - Lianne Gonsalves; Erin C. Hunter; Vanessa Brizuela; Joseph D. Tucker; Megan L. Srinivas; Evelyn Gitau; Catherine H. Mercer; Nathalie Bajos; Debbie Collins (BMC, 2021)
Plain language summary Sexual and reproductive health receives a lot of attention, globally. Much of this attention focuses on research and clinical services to address health outcomes. Behavioural issues known to be closely linked to health outcomes-that is people's sexual activity and sexuality-tend to be overlooked. In many countries, there is very little data about people's sexual practices and behaviours. If this information were available, then sexual and reproductive health programmes could be planned to better meet the needs of populations. Therefore, the World Health Organization developed a survey instrument which can be used to ask people around the world about their sexual practice and behaviours. The protocol described here will test the draft survey instrument in different countries to make sure that people from diverse backgrounds understand each survey question in a comparable way. The study uses 'cognitive interviewing', a qualitative method where researchers ask participants about their thought processes in reading a question and providing an answer while they complete a survey. Up to 20 countries will participate in this study, with five or more completing the research at a time in each study wave. Country teams in each wave will translate the survey instrument (if necessary), conduct the cognitive interviews, revise the instrument based on the findings, and if needed, conduct more interviews in their setting with the revised survey instrument. The result of this research will be a survey instrument that has been tested in a variety of languages and settings and is ready to be used in different contexts, globally.